Zn(II)-cyclam based chromogenic sensors for recognition of atp in aqueous solution under physiological conditions and their application as viable staining agents for microorganism - Mahato, Prasenjit; Ghosh, Amrita; Mishra, Sanjiv K.; Shrivastav, Anupama; Mishra, Sandhya; Das, Amitava (Inorganic Chemistry, 2011)
Two chromogenic complexes, L.Zn (where L is (E)-4-((4-(1,4,8,11-tetraazacyclotetradecan-1-ylsulfonyl)phenyl)diazenyl)-N,N-dimethylaniline) and its [2]pseudorotaxane form (α-CD.L.Zn), were found to bind preferentially to adenosine triphosphate (ATP), among all other common anions and biologically important phosphate (AMP, ADP, pyrophosphate, and phosphate) ions in aqueous HEPES buffer medium of pH 7.2. Studies with live cell cultures of prokaryotic microbes revealed that binding of these two reagents to intercellular ATP, produced in situ, could be used in delineating the Gram-positive and the Gram-negative bacteria. More importantly, these dyes were found to be nontoxic to living microbes (eukaryotes and prokaryotes) and could be used for studying the cell growth dynamics. Binding to these two viable staining agents to intercellular ATP was also confirmed by spectroscopic studies on cell growth in the presence of different respiratory inhibitors that influence the intercellular ATP generation.